Thieme atlas of anatomy general anatomy and musculoskeletal system - Scheunke, Michael; Schulte, Erik; Schumacher, Udo (Thieme, 2006)
The THIEME Atlas of Anatomy integrates anatomy and clinical concepts. It features: organized intuitively, with self-contained guides to specific topics on every two-page spread; hundreds of clinical applications integrated into the anatomical descriptions, emphasizing the vital link between anatomical structure and function; beautifully illustrated with expertly rendered digital watercolors, cross-sections, x-rays, and CT and MRI scans; clearly labeled images help you easily identify each structure; summary tables throughout - ideal for rapid review; and with 1,700 newly created illustrations and 100 tables, this work features comprehensive coverage of the musculoskeletal system and general anatomy, in addition to embryology and surface anatomy.